1998
DOI: 10.1021/es9704996
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Different VOC onto Soil Minerals from Gas Phase:  Influence of Mineral, Type of VOC, and Air Humidity

Abstract: The adsorption of volatile organic compounds (VOC) onto soils plays an important role in the mobility of these kinds of contaminant through soils. It is therefore of interest to learn more about the mechanisms of interaction between VOC and soil particles. An experimental study has been carried out in order to determine the adsorption isotherms of volatile organic gases of different properties on soil minerals of different characteristics, working in a wide range of compound concentrations. The adsorption of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 32 publications
(63 reference statements)
6
73
0
Order By: Relevance
“…Besides vertical diffusion, adsorption onto colloids (polar particles) within the media could slow down or stop both vertical and horizontal diffusion. Although adsorption is expected to be relatively low in sand (Ruiz et al 1998), silicates on the surface of sand particles, and also the aqueous phase of the medium, could adsorb many of the compounds that were tested. This was evident from a study in which a blend of induced maize volatiles was pushed through a silica-filter, and several of the volatiles that did not diffuse in the current study were found trapped on the filter (D'Alessandro and Terpenes were the best diffusing compounds, possibly explaining why WCR-damaged maize roots exude mainly terpenes, even though maize is able to synthesize many other VOCs (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Besides vertical diffusion, adsorption onto colloids (polar particles) within the media could slow down or stop both vertical and horizontal diffusion. Although adsorption is expected to be relatively low in sand (Ruiz et al 1998), silicates on the surface of sand particles, and also the aqueous phase of the medium, could adsorb many of the compounds that were tested. This was evident from a study in which a blend of induced maize volatiles was pushed through a silica-filter, and several of the volatiles that did not diffuse in the current study were found trapped on the filter (D'Alessandro and Terpenes were the best diffusing compounds, possibly explaining why WCR-damaged maize roots exude mainly terpenes, even though maize is able to synthesize many other VOCs (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this and despite microbial VOC production, plain soil (without plant roots) is reported to be a VOC sink, strongly dependent on soil temperature and moisture (Asensio et al 2007a). Volatile organic compound sorption to clay minerals (Petersen et al 1995;Chen and Wu 1998;Ruiz et al 1998;Poulsen et al 1998;Serrano and Gallego 2006), solubilisation in the soil aqueous phase (Asensio et al 2007a) or degradation by other microorganisms (Cleveland and Yavitt 1998;Smolander et al 2006;Owen et al 2007;Insam and Seewald 2010) may explain any soil net VOC uptake or variations between replicates (Leff and Fierer 2008). Microbial VOCs may derive from many different metabolic sources, such as primary metabolism like end products of fermentative pathways such as ethanol (ethanol fermentation), butyric acid and acetone (butyric acid fermentation) and as volatile intermediates of aerobic or anaerobic detritus decomposition (Castaldelli et al 2003;Karl et al 2003).…”
Section: Microbial Growth and Voc Productionmentioning
confidence: 97%
“…Given that a volatile compound must be perceived at a physiologically active concentration by a neighbouring plant before it can be considered as a signal mediating plant-plant interactions (Firn and Jones 1995;Preston et al 2001), the environmental fate of root-emitted VOCs in the soil is of crucial importance and will be linked to their chemical stability, their production rate by plant roots, and their interactions with the solid, liquid and gaseous components of the soil ecosystem (Perry et al 2007;Zeng 2014). For instance, they can be diluted in the gaseous phase of the soil matrix, solubilized into the soil solution (particularly polar oxygenated VOCs) (Fischer et al 1994;Hiltpold and Turlings 2008;Peñuelas et al 2014), used as a carbon source by soil microorganisms (Misra et al 1996;Cleveland and Yavitt 1998;Kleinheinz et al 1999;Ramirez et al 2009), adsorbed into soil particle surfaces (Inderjit and Dakshini 1995;Ruiz et al 1998) or subjected to physico-chemical degradation (Perry et al 2007). Taken together, these phenomena lead to a decrease in VOC concentration with increasing distance from the source.…”
Section: Environmental Fate Of Root-emitted Vocsmentioning
confidence: 99%